Phytochemical Studies On Elytraria Acaulis - N. KIRUTHIKA; R.DHIVYA; K.KALAISELVI; P.KANIMOZHI; K.PANNEERSELVAM. (International Journal of Pharma and Bio Sciences, 2012)
The plant Elytraria Acaulis belonging to the family Acanthaceae. The plant mostly found in hills. Stem less perennial herb with 1-several unbranched flowering stems up to c-30CM tall. Leaves in a basal rosettle, subsessile, elliptic to obovate, up to 18cm long, hairy, particularly on the veins. Flowers in 1-several spikes held in tight apiculate, overlapping bracts. Bracts and flowering stem bluish green. Corolla white, lower lip and lateral lobes spreading, 2- Lobed flowers often not opening capsule 5.5-6.5mm long hairless. The phytochemical screening of methanol extract shows the presence of chemical compound like Alkaloids, Flavonoids, Protein, Amino Acid, Glycosides, Carbohydrates, Phenol, Steroids, Saponins and Tannins. The chromatographic studies give various spots (Hptlc)with methanol extract may confirm the presence of alkaloidal contents in the plant.